The Bhagavad Gita: A Biography by Richard H. Davis - Rodrigues, Hillary (Religious studies and theology, 2015)
The Bhagavad Gita: A Biography by Richard H. Davis. Princeton University Press, 2015. 243pp., 15 b/w illustrations. Hb., $24.95. ISBN-13: 9780691139968.